Mitos, Stress Serta Dukungan Keluarga Pada Perempuan Primigravida Jawa - Inggrit Mareta Walanda; Desi Desi; Kristiani Desimina Tauho (Jurnal Keperawatan Muhammadiyah, 2021)
Background:Pregnancy is one of the most awaited phases of life for most women and couples, but for some, pregnancy can cause anxiety over the changes that occur physically and psychologically. Myths surrounding pregnancy and childbirth are one of the greatest environmental influences on the health of pregnant women from a cultural point of view. Myths related to pregnancy generally regulate prohibitions, recommendations or obligations or obligations that must be carried out by a woman during pregnancy. The purpose of this study was to find out about the myths related to pregnancy from the perspective of Javanese culture, how these myths affect the stress level of pregnant women and how to support family during pregnancy. Method This study involved 5 participants using interviews. The results of the study found that there are myths that are still carried out from generation to generation in the family, especially those related to pregnancy. The existing myths are basically understood and implemented by avoiding taboos. Avoiding taboos such as, pregnant women are prohibited from going out at night, pregnant women are prohibited from bathing at night, pregnant women are prohibited from killing animals, are required to bring sharp objects such as scissors or safety pins, have the belief to bring goodness/safety to pregnant women and the baby in the womb Families of pregnant women also play a role in providing support to pregnant women so that taboos can be carried out properly because this has become a belief from their ancestors. Conclusion: Primigravida mothers do not object to the myths that develop in the family because they have become ancestral traditions and beliefs. The family is also considered to provide full support during pregnancy by adhering to taboos.Keywords: Myth, Stress, Family Support, Pregnant Women